Accessing drug treatment courts do age, race or gender matter? - Weinrath, Michael (The Australian and New Zealand journal of criminology, 2018)
To ensure equitable access to diversion from custody, Canadian drug treatment courts should accept referrals whose age, gender, and Indigenous race proportions are similar to probation or custody admissions. Of particular concern are Indigenous offenders, who are over-represented in Canada’s community and institutional corrections systems. To examine the influence of these extra-legal factors, we assessed referrals to the Winnipeg, Manitoba drug treatment court (N = 288). Provincial corrections data from Statistics Canada’s adult key indicator report, eight years of official records drug court data (2006-2014), and local male sentenced inmate admission data were analyzed. Age, gender, and Indigenous status did not influence referral. Indigenous male referrals to the drug treatment courts were generally higher risk than females or other males. Correctional institutions data showed that Indigenous male inmates had more convictions for violence and higher street gang membership rates, thus attempting to increase drug court referral poses significant challenges. In Manitoba, substantial custody reductions of offenders overall and Indigenous male offenders in particular will require more radical solutions than the drug court.